Influence of Investment, Disinfection, and Storage on the Microhardness of Ocular Resins - Goiato, Marcelo Coelho [UNESP]; Santos, Daniela Micheline dos [UNESP]; Gennari-Filho, Humberto [UNESP]; Zavanelli, Adriana Cristina [UNESP]; Dekon, Stefan Fiuza de Carvalho [UNESP]; Mancuso, Daniela Nardi [UNESP] (Wiley-Blackwell, 2009)
Purpose: The longevity of an ocular prosthesis is directly related to the resistance to erosion of its material. The purpose of this study was to evaluate the effects of chemical disinfection and the method of investment on the microhardness of ocular prosthesis acrylic resin.Materials and Methods: Thirty-two test specimen investments were obtained in two silicones. A segment was cut in each test specimen, and each specimen was fixed in an acrylic disk. The specimens were then polished and submitted to the first microhardness test before immersion in distilled water and incubation for 2 months. During this 2-month period, the specimens were immersed in a water bath at 37 degrees C and were disinfected daily; half were disinfected with neutral soap and the other half were disinfected with 4% chlorhexidine gluconate. After the storage phase and disinfection, a second microhardness test was performed. The surface microhardness values for the acrylic resins were submitted to ANOVA, followed by the Tukey test.Results: The disinfection and the period of storage did not statistically influence the surface microhardness of the acrylic resin, independent of the method of investment of the specimens (Zetalabor or Vipi Sil). The investment of specimens with Zetalabor silicone presented a greater surface hardness, independent of the type of disinfection and the period of storage.Conclusions: Based on these results, we suggest that the microhardness of the resin evaluated was not influenced by the method of disinfection or the time of storage used and was affected only by the investment material.
Keywords: Acrylic resins; facial prostheses; hardness